Factors Associated with In-hospital Mortality in Patients with Acute Coronary Syndrome - Hiradipta Ardining; Nisa Amnifolia Niazta; Muchammad Dzikrul Haq Karimullah (Heart Science Journal, 2022)
BACKGROUND: Acute coronary syndrome (ACS) remains major cause of death worldwide, therefore it is important to determine factors associated with worse outcomes to better elucidate which patients deserve a more aggressive approach for management. OBJECTIVES: To describe the characteristics of patients admitted with ACS to Kediri General Hospital and factors associated with in-hospital mortality in ACS patients.METHODS: In this cross-sectional study, 117 patients who admitted with ACS to Kediri General Hospital between January and June 2020 were included. Data were collected retrospectively from medical records and analyzed using SPSS software v25.RESULTS: During hospitalization, 18 (15,4%) died. The bivariate analysis showed the patients who died were predominantly female, had higher prevalence of Killip IV, higher prevalence of clinical signs of heart failure, lower admission systolic and diastolic blood pressure, and higher heart rate. From multivariable analysis, variables which were significantly associated with in-hospital mortality were decreased consciousness (OR 11, 95% CI 1.327-92.4, p=0.026), and Killip class IV (OR 9.558, 95% CI 2.016-45.317). CONCLUSION: Decreased consciousness and Killip class IV were associated with increased inhospital mortality in ACS.KEYWORDS:In-hospital mortality, acute coronary syndrome, Killip class, Decrease of Conciousness